2009
DOI: 10.1111/j.1365-2435.2009.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Out in the cold: physiological capacity influences behaviour in deer mice

Abstract: Summary 1.Understanding the links between physiological performance and fitness is key to predicting the responses of individuals to environmental change, especially that imposed by climate. Of particular interest are traits linked with metabolic performance. In particular, maximal metabolic rate (MMR; which describes the upper limit to heat production) and basal metabolic rate (BMR; which describes the lower limit to heat production for a normothermic endotherm) are important causal mechanisms that determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…Energy budget in cold-exposed mice increasing feeding time (Johnson and Cabanac, 1982;Perrigo Bronson, 1985;Schwaibold and Pillay, 2006). Also in deer mice (Peromyscus maniculatus), the duration of activity per bout decreased at colder temperatures, and the amount of time spent active in the cold was negatively correlated with ambient temperature (Sears et al, 2009). Consistently, in the current study cold-exposed mice showed a reduction in the time spent on activity and exhibited increases in the time spent on feeding and resting behavior.…”
Section: Behaviorsupporting
confidence: 75%
“…Energy budget in cold-exposed mice increasing feeding time (Johnson and Cabanac, 1982;Perrigo Bronson, 1985;Schwaibold and Pillay, 2006). Also in deer mice (Peromyscus maniculatus), the duration of activity per bout decreased at colder temperatures, and the amount of time spent active in the cold was negatively correlated with ambient temperature (Sears et al, 2009). Consistently, in the current study cold-exposed mice showed a reduction in the time spent on activity and exhibited increases in the time spent on feeding and resting behavior.…”
Section: Behaviorsupporting
confidence: 75%
“…In birds, a decrease in abdominal temperature of the Gentoo penguin (Pygoscelis papua) was linked to reduced energetic costs while diving for prey (Bevan et al 2002). Also, deer mice (Peromyscus maniculatus) that consumed more food exhibited higher maximal metabolic rates that resulted in higher rates of activity in cold conditions, illustrating how behavioral decisions and physiological capacities influence the potential for energetic gain (Sears et al 2009). Thus, any variation in physiological traits that influence activity has direct implications for predicting the relationship between an organism and its environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies of physiological diversity may reveal the physiological basis of intraspecific variation in life history traits (Speakman, 2005;Arnott et al, 2006;Williams, 2012). Finally, phenotypic diversity may be indicative of genetic diversity and the degree to which a population can adjust to environmental change (Hayes and Jenkins, 1997;Bolnick et al, 2003;Sears et al, 2009).…”
Section: Introductionmentioning
confidence: 99%